Vascular comorbidities in patients with multiple sclerosis and their impact on physical disability - Daliborka Tadić; Sanja Grgić; Aleksandra Dominović-Kovačević; Majda Nazalević-Bursać; Srđan Mavija; Vlado Đajić (Medicinski glasnik, 2022)
Aim: Given the impact of vascular comorbidities (VC) on the diagnosis, treatment, and outcome of multiple sclerosis (MS), we examined the incidence and correlation of VC and risk factors for vascular disease in people with MS (PwMS) compared to the general population, and the impact on the physical disability of patients. Methods: Cross-sectional study involved 100 patients with MS and 50 healthy people from the general population, matched by sex and age. The values of demographic, biochemical, and anthropometric parameters, the presence of VC and risk factors for vascular diseases in both groups, and clinical parameters in PwMS were analysed. Statistical analysis included methods of descriptive statistics, χ2 test, Student's t-test, analysis of variance, correlation and regression analysis. Results: Groups differed by a higher frequency of transient ischemic attack in the control group (p=0.024), and the treatment of hypertension (p=0.038) and smoking frequency (p=0.044) in the MS group. Normal triglycerides levels were statistically significantly more prevalent in the MS group (p=0.000). Total body weight and BMI were statistically significantly higher in the control group (p=0.000). The increase in Expanded Disability Status Scale (EDSS) score was associated with higher levels of total (p=0.001) and low-density lipoprotein (LDL) cholesterol (p=0.003), and activated partial thromboplastin time APTT (p=0.002). Conclusion: In PwMS it is necessary to pay attention to the higher frequency of smoking than in general population, and the impact of total cholesterol, LDL and APTT levels as significant parameters that affect physical disability.
Keywords: cholesterol; hypertension; smoking; vascular diseases